Asset Intelligence through Integration and Interoperability and Contemporary Vibration Engineering Technologies Proceedings of the 12th World Congress on Engineering Asset Management and the 13th International Conference on Vibration Engineering and Technology of Machinery - Mathew, Joseph; Lim, C.W.; Ma, Lin.; Sands, Don.; Cholette, Michael E.; Borghesani, Pietro; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
These proceedings include a collection of papers on a range of topics presented at the 12th World Congress on Engineering Asset Management (WCEAM) in Brisbane, 2 - 4 August 2017. Effective strategies are required for managing complex engineering assets such as built environments, infrastructure, plants, equipment, hardware systems and components. Following the release of the ISO 5500x set of standards in 2014, the 12th WCEAM addressed important issues covering all aspects of engineering asset management across various sectors including health. The topics discussed by the congress delegates are grouped into a number of tracks, including strategies for investment and divestment of assets, operations and maintenance of assets, assessment of assets' health conditions, risk and vulnerability, technologies, and systems for management of assets, standards, education, training and certification. .
Keywords: Security systems; Technological innovations; Industrial Management; Manufactures; Security Science and Technology; Innovation and Technology Management; Industrial Management; Machines, Tools, Processes